Meniere’s disease in the pediatric age group-a review - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2022)
Meniere’s disease (MD) is an uncommon clinical entity in the pediatric age group. Patients of MD often present with typical Meniere’s triad of cochlear sensorineural hearing loss, tinnitus, and intermittent vertigo attacks lasting from minutes to hours. As children are often unable to communicate effectively about the symptoms, they do not initially meet the requirements for the diagnosis of MD. It is a chronic inner ear disease that severely affects the quality of life including schooling among children.MD of children often remains a diagnostic dilemma that challenges clinicians for its management. Proper history taking and diagnostic criteria are helpful for diagnosis with early treatment of MD and improve the quality of life. There are several therapeutic options available for MD, but no one is considered a highly effective modality for the cure of the MD. The primary purpose of the medical treatment of MD is to treat his or her symptoms rather than disease. Betahistine and diuretics are usually effective medical treatments for controlling vertigo in MD. There are several reports in favor of intratympanic use of aminoglycosides for the control of vertigo. Endolymphatic sac decompression is a surgical treatment option in the case of medically intractable MD. Vestibular neurectomy and labyrinthectomy are two important surgical techniques for the treatment of disabling vertigo of MD, but these surgical procedures are associated with relatively higher surgical morbidity. The objective of this review article is to discuss MD in the pediatric age group including its epidemiology, etiopathology, clinical manifestations, diagnosis, and current treatment options to relieve disabling symptoms of MD and so improving the quality of life of children.